Seed disperser connectivity in a heterogeneous landscape of the Colombian Coffee Region - Isabel Cristina Restrepo-Carvajal; Nicola Clerici; Swanni T. Alvarado (PLoS ONE, 2026)
Habitat fragmentation is a major threat to biodiversity in tropical montane ecosystems, where limited forest cover and steep elevational gradients can strongly constrain species movement and connectivity between habitat fragments. We assessed landscape fragmentation, functional connectivity of habitat patches for four seed-dispersing mammals (i.e., the capacity of species to move among habitat patches), and conservation priorities in the Colombian Coffee Region, a highly transformed Andean landscape. Using resistance-based distance matrices, graph-based landscape connectivity indices (PC, dPC, and ECA) and sensitivity analyses across resistance and dispersal scenarios we quantified species-specific connectivity, identified key habitat nodes, and evaluated their representation within the current protected area network. We also incorporated uncertainty into a multi-species prioritization framework to improve conservation decision-making. Forest cover is highly reduced (remains 18.9% of its original extent) and severely fragmented, resulting in low functional connectivity to all species. Connectivity patterns were primarily associated with species’ elevational range rather than home range size, with generalist species maintaining higher connectivity than species restricted to narrower elevations. Connectivity was highly uneven, with a small number of habitat patches acting as critical network hubs whose loss could substantially reduce overall connectivity. Despite their importance, more than half of the total habitat and many high-priority connectivity areas remain outside protected areas, revealing a strong mismatch between conservation priorities and current protection coverage. Incorporating uncertainty further refines prioritization by distinguishing robust conservation targets from areas requiring additional empirical validation. Our results demonstrate that integrating multi-species connectivity modeling with uncertainty analysis provides a robust framework for identifying conservation priorities. These findings are particularly relevant for vulnerable and range-restricted species such as Cebus versicolor and emphasize the need for restoration and connectivity-oriented conservation strategies in human-modified tropical landscapes.